Regulação do Mercado de Valores Mobiliários: da teoria de comando e controle à teoria de regulação responsiva - Zakia, Maria Lucia Perez Ferres (2024)
In recent years, federal regulatory entities, such as the Securities and Exchange Commission, have changed the regulatory approach, initially based on a repressive culture of command and control, to incorporate concepts and rationale typical of responsive regulation, contextualizing sanctioning activity to a logic of intrinsic incentives and granting greater discretion to the regulator to construct and apply more individualized state responses, responsive to the concrete behaviors of those regulated and aligned with the purposes of the underlying regulatory state policy. The change in regulatory perspective is neither explicit nor integral, but materializes through the tacit and often uncoordinated adoption of scattered concepts. The regulator's discretion, necessary in responsive regulation, is seen in the issuance of normative acts, in the interpretation and application of the norm to allow regulatory management. The question arises about the compatibility of the dynamics of responsive regulation with a civil system, in particular, with the constitutional principles of Brazilian public administration. It is proposed to analyze the national legislation that would make up a microsystem applicable to sanctioning regulatory activity, from a responsive perspective, and analyze whether the CVM complies with these standards. From a bibliographical and jurisprudential research, data collection from the CVM and the external control body, it appears that it is possible to analyze the current CVM regulatory sanctioning legislation from the perspective of the theory of responsive regulation. A simulation of the regulatory pyramids applicable to the regulation of investment funds is presented with the aim of demonstrating how the rules and responsive regulatory dynamics would remain organized within the scope of the CVM's regulatory sanctioning activity. It is concluded that there is no legislative and theoretical resistance to the adoption of the theory of responsive regulation within the scope of regulatory sanctioning activity incident on the Brazilian securities market, as long as the assumptions contained in the legislation are respected and that regulatory decisions are based on reasonable interpretation of the law and the Federal Constitution, exposing motivation in an explicit, individualized, congruent, public and coherent way with the adopted regulatory model